Pyrazoles in the Intersection of Mesomeric Betaines and N-Heterocyclic Carbenes: Formation of NHC Selenium Adducts of Pyrazolium-4-aminides - Hillrichs, Kai; Namyslo, Jan C.; Lederle, Felix; Hübner, Eike G.; Schmidt, Andreas (Synthesis, 2022)
Starting from 4-nitropyrazole, eight mesoionic pyrazolium-4-aminides were prepared by a six-step reaction sequence. The deprotonation of 1,2-disubstituted 4-amido-1H-pyrazolium salts by an anion exchange resin in its hydroxide form is the final step of the synthesis. A tautomeric equilibrium between the mesoionic compounds (pyrazolium-4-aminides) and N-heterocyclic carbenes (pyrazol-3-ylidenes) can be formulated; however, the NHC tautomers were not detected by means of NMR spectroscopy in polar aprotic solvents such as DMSO-d6 or MeCN-d3. Apart from tautomerism, anionic N-heterocyclic carbenes can be formulated as a result of a deprotonation of the mesoionic compounds. Trapping reactions were performed with selenium, which resulted in the formation of pyrazole-3-selenones. Methylation at the selenium atom gave the corresponding 3-(methylselanyl)-4-amido-1H-pyrazolium salts, which were deprotonated to give new mesomeric betaines, 3-(methylselanyl)-1H-pyrazolium-4-aminides as unique compounds. DFT-calculations as well as 77Se NMR spectroscopic measurements were carried out.
Keywords: pyrazol-3-ylidenes; mesoionic compound; pyrazol-3-selenone; selenium ether; 77Se NMR; selone; mesoionic imine